Relationship of Serum Soluble Klotho Levels and Echocardiographic Parameters in Patients on Maintenance Hemodialysis - Ai-hua Zhang; Wei-kang Guo; Ling Yu; Wen-hu Liu (Karger Publishers, 2019)
Background: Cardiovascular disease is the leading cause of morbidity and mortality in maintenance hemodialysis (MHD) patients. Uremic cardiomyopathy, characterized by myocardial hypertrophy and fibrosis, has a significant contribution to these adverse cardiac outcomes. The protective effect of soluble Klotho (s-Klotho) on myocardial damage was demonstrated in in vitro and animal experiments. However, data from MHD patients is limited. The present study was designed to identify potential correlations between echocardiographic parameters and serum s-Klotho levels in MHD patients. Methods: This is a cross-sectional study involving 105 MHD patients from the Dialysis Center of Capital Medical University affiliated Beijing Friendship Hospital between March and October 2014. The general information for each patient was recorded. Fasting blood samples were collected prior to hemodialysis during the mid-week session in all patients. The echocardiogram and left lateral lumbar spine radiograph were performed after the same mid-week session. The dialysis records for each session within 3 months before the blood tests were documented. According to the quartiles of s-Klotho levels, patients were divided into four groups (Group 1-4). The demographic and clinical characteristics, echocardiographic parameters, and abdominal aortic calcification scores among the groups were compared. Results: The enrolled 105 patients were predominantly male (54.3%) with an average age of 59.9 ± 11.2 years. Previous hemodialysis durations were 76 (42-133) months. Sixteen (15.2%) patients had diabetes mellitus. Mean serum s-Klotho level was 411.83 ± 152.95 pg/mL, and the 25th percentile, 50th percentile, and 75th percentile values of serum s-Klotho levels were 298.9, 412, and 498.2 pg/mL, respectively. Individuals in the bottom quartile of s-Klotho levels (Group 1) had significantly increased interventricular septal thickness (IVST) compared to those in the other three quartiles of s-Klotho levels (Group 1: 1.12 ± 0.16 cm; vs. Group 2: 1.12 ± 0.16 cm, p = 0.008; vs. Group 3: 0.94 ± 0.13 cm, p < 0.001; vs. Group 4: 1.03 ± 0.1 5 cm, p = 0.022). There were significant differences in the ratios of IVST and posterior wall thickness (PWT) between patients of Group 1 and Group 3 (1.12 ± 0.1 2 vs. 1.00 ± 0.1 4, p = 0.004). No significant differences were found for other parameters among the groups. The univariate correlation analyses showed that gender (r = -0.211, p = 0.030), Kt/V urea (r = -0.240, p = 0.014), hypersensitive C reactive protein (hs-CRP) (r = 0.196, p = 0.045), and serum s-Klotho levels (r = -0.260, p = 0.007) significantly correlated with IVST. Ultimately, only hs-CRP and serum s-Klotho levels were entered into a multiple regression model. Conclusions: The present study showed that patients with lower circulating s-Klotho levels were more often associated with larger IVST and greater ratios of IVST and PWT. There was an independent association between s-Klotho and IVST, and lower s-Klotho levels seem to be a potential risk factor of uremic cardiomyopathy in MHD patients.